PENGARUH DEWAN KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJERIAL DAN LEVERAGE TERHADAP MANAJEMEN LABA - Hena Arfiana; Nani Rohaeni; Amyati Amyati (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
Earnings management arises because of pressure from both inside and outside the company. Several factors that can influence management include: independent board of commissioners, managerial ownership and leverage. This study aims to determine the effect of independent commissioners, managerial ownership and leverage on earnings management in retail trading sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period partially and simultaneously. This research was conducted using a quantitative descriptive method with a population of 27 retail trading sub-sector companies that are incorporated in the Indonesia Stock Exchange for the 2015-2019 period and taken as many as 7 companies using purposive sampling. retail trade sector for the 2015-2019 period. Based on the results of the t-test (partial) the independent board of commissioners has a value of -tcount < -ttable where -3.520 < -2.03951 with a sig value of 0.001 <0.05, meaning that the independent board of commissioners has a negative and significant effect on earnings management. Managerial ownership has a value of -tcount < -ttable where -4.364 < -2.03951 with a sig value of 0.000 <0.05, meaning that managerial ownership has a negative and significant effect on earnings management. Leverage has tcount > ttable where 3.188 > 2.03951 with a sig value of 0.003 < 0.05, meaning that leverage has a positive and significant effect on earnings management and the results of the F (simultaneous) test Fcount > Ftable and a value where 12.940 > 2.90 with sig 0.000 < 0.05 means that the board of commissioners is independent, managerial ownership and leverage affect earnings management